The Study Examines Perlocutionary Speech Acts in TikTok Comments by @resep_debm and Their Relevance to Indonesian Language Learning - Megarizki, Berlianing; Prayitno, Harun Joko (Universitas Muhammadiyah Surakarta, 2023)
This research aims to (1) describe the forms of perlocutionary speech acts in the comment section of the TikTok account @resep_debm, and (2) analyze the relevance of perlocutionary speech acts to Indonesian language learning. The data source for this study is the TikTok account @resep_debm, and the data consists of utterances or expressions in the comment section. The method used in this research is qualitative descriptive. The data collection technique is note-taking, and the data analysis technique is Morris's pragmalinguistic model, involving data collection, selection, simplification, grouping, analysis, and presentation. The results of this study indicate the presence of perlocutionary speech acts in the comment section of TikTok @resep_debm, with 24 data comprising expressive speech acts (14), directive speech acts (5), and representative speech acts (5). The dominant perlocutionary speech act used by the audience in the comment section of the TikTok account @resep_debm is expressive speech acts, accounting for 14 data. On social media, many people tend to follow the crowd when it comes to commenting, which should be a particular concern in the field of education. The connection between expressive speech acts and the formation of students' moral values lies in the demand for teachers to educate students to have good morals. Teachers must teach students how to comment appropriately, especially on social media, and use polite language. Additionally, parents are also urged to monitor their children's use of social media to prevent them from falling into harmful behaviors that could adversely affect themselves and others.